Sacral epiduroscopic laser decompression for complex regional pain syndrome after lumbar spinal surgery: A case report. Issue 19 (May 2018) - Jung, Jae-Wook; Kim, Yong Han; Kim, Hyojoong; Kang, Eunsu; Jo, Hyunji; Ko, Myoung Jin
Abstract: Rationale: CRPS after a lumbar surgery has symptoms that are similar to PSSS. However, standard criteria for distinguishing CRPS from PSSS do not exist. We present a case report of a 31-year-old female with CRPS symptoms after lumbar spinal surgery treated by performing SELD. Patient concerns: This patient was referred to our pain clinic for left ankle pain. She received a lumbar discectomy for a herniated lumbar disc (L5/S1) but the pain was aggravated after surgery. Diagnoses: The characteristics of the pain were burning, tingling, and cold, and were accompanied by other symptoms such as swelling, color change and mail dystrophy. The patient was diagnosed with CRPS. Interventions: Medications and interventional therapies were not effective in reducing pain. SELD was performed and severe adhesive inflammation was observed in the L4-S1 epidural space. We performed mechanical adhesiolysis and injected hyalurodinase and dexamethasone near the L5 and S1 root. One month after, a second SELD was performed as same manner. Outcomes: After second SELD, the patient's pain markedly decreased. On the second visit in the outpatient clinic, the patient was absent of pain without any other medications. Lessons: CRPS like symptoms can appear after lumbar spinal surgery due to adhesion and inflammation in the epidural space. In such cases, SELD can be considered as diagnostic and therapeutic option.